ANALISIS PENERAPAN AKUNTANSI PERSEDIAAN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN MINAHASA - Waworega, Aprillinda Angie; Manossoh, Hendrik; Tangkuman, Steven J. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Human Resources and Human Resource Development Agency of Minahasa Regency is a supporting element of the Bupatis duties, led by the Head of the Agency, which is located below and the responsibility to the Regent through the Regional Secretary. Inventories are current assets in the form of goods or equipment to support activities operations of the government and the stuff that meant to be sold and / or delivered into service to the public. The purpose of this study is to know whether the implementation of inventory accounting applied to Human Resources Agency and Human Resource Development of Minahasa Regency is in accordance with Statement of Government Accounting Standard Number 05 (PSAP 05). The method used is interview and literature study. The methotds analysis data is used descriptive qualitative. The results of this study indicate that inventory accounting at Human Resources Agency and Human Resource Development of Minahasa Regency is mostly appropriate. However, inventory recognition with load approach has not used the accrual basis.Keywords: Government Accounting, Inventory Accounting, PSAP No.05.